Rous sarcoma virus infection of synchronized cells establishes provirus integration during S-phase DNA synthesis prior to cellular division. - Humphries, E H (1981)
Synchronized chicken embryo fibroblasts, prepared by addition of serum to stationary cells arrested in Go, were exposed to the Prague strain of Rous sarcoma virus. At different times during the cell cycle, high molecular weight DNA was prepared from infected cells and examined for the presence of newly integrated viral DNA sequences. The results demonstrate that newly integrated viral sequences were first detected during S-phase DNA synthesis 9 hr after infection. The presence of colchicine prevented cellular division and delayed the appearance of progeny virus but it did not affect the appearance of viral specific DNA in the high molecular weight fraction of cellular DNA. Our results indicate that provirus integration, occurring during S-phase DNA synthesis, does not require cell division. Previous experiments have demonstrated that Rous sarcoma virus infection of chicken embryo fibroblasts requires cell division to initiate viral RNA synthesis and the production of progeny virus. The findings presented in this report support the hypothesis that division of the infected cells is required for an event that controls viral expression at the level of the integrated provirus.